EVALUATION AND IMPLEMENTATION STRATEGY OF SLUM HANDLING CASE STUDY LOMBOK DISTRICT EAST NUSA TENGGARA BARAT - Ahmad Amrullah; Akmaluddin Akmaluddin; Suryawan Murtiadi (International Journal of Social Science, 2022)
The Uninhabitable Houses Program (RTLH) is a DPRRI Commission VIII program in partnership with the Ministry of Social Affairs. The RTLH processing that will be carried out in 2021 will be divided into several sub-districts in East Lombok Regency, namely Sakra, East Sakra, West Sakra, Keruak and Jerowaru Districts. However, due to budget constraints, especially the Covid 19 outbreak in 2021, the proposal could not be completed, so it was rescheduled in 2022 to complete the RTLH in East Lombok Regency which is in several of the same sub-districts. The purpose of this research is to determine the priorities for the construction of infrastructure for uninhabitable housing (RTLH) and to determine the weight of the criteria that influence decisions in determining where assistance is prioritized. Evaluation of the management of the 2021 RTLH in several districts/cities is carried out on the development process of RTLH both from the inhibiting factors and the supporting factors. The evaluation of the Uninhabitable Houses Reconstruction Program (RTLH) includes determining the target beneficiaries, the process of implementing the RTLH program, evaluating the reporting of the results of the implementation of the RTLH program. Internally, the inhibiting factor for the implementation of the RTLH program is the lack of competent staff to prepare reports, while externally there is a shortage of construction workers. An uninhabitable house, hereinafter referred to as RTLH, is a place to live that does not meet health, safety and social requirements. Therefore, East Lombok Regency requires special treatment in building uninhabitable houses to overcome the problem of slum settlements